Multidisciplinary Information Retrieval 5th Information Retrieval Facility Conference, IRFC 2012, Vienna, Austria, July 2-3, 2012 Proceedings - Salampasis, Michail; Larsen, Birger; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the proceedings of the 5th International Information Retrieval Facility Conference, IRFC 2012, held in Vienna, Austria, July 2-3, 2012. The 12 papers presented were carefully reviewed and selected from 17 high-quality submissions. IRF conferences wish to bring young researchers into contact with industry at an early stage. This fifth conference aimed to tackle four complementary research areas: information retrieval, machine translations for search solutions, and interactive information access. The papers are organized into topical sections on patent search, Web search, applications, and query formulation and analysis.
Keywords: Computer science; Data mining; Information storage and retrieval; User interfaces (Computer systems).; Artificial intelligence; Computer Science; Information Storage and Retrieval; Data Mining and Knowledge Discovery; Information Systems Applications (incl. Internet).; User Interfaces and Human Computer Interaction; Artificial Intelligence (incl. Robotics).; Electronic books